Analysis of the Role of Oil Palm Plantation Sub-Sector in Gross Regional Domestic Product of West Kalimantan Province - Duta, Caroline Laura; Wuri, Josephine; Budisusila, Antonius; Harnoto, Laurentius Bambang (Eduvest - Journal of Universal Studies, 2025)
Oil palm plantations are a very important commodity in their role, especially in supporting the country's economy, creating jobs and increasing people's income in plantation commodity-producing areas. This study aims to analyze the role of the oil palm plantation subsector in the Gross Regional Domestic Product of West Kalimantan Province. The data used in this study is annual secondary data on oil palm production volume, number of labor, and Gross Regional Domestic Product of West Kalimantan Province during the 2018-2023 period. The research method used is the fixed effect panel data regression analysis method . The results of this study show that the role of the oil palm plantation subsector in the Gross Regional Domestic Product of West Kalimantan Province is positive and significant. This can be seen from the influence of the volume of palm oil production and the number of workers on the GDP of West Kalimantan Province is positive and significant both partially and simultaneously.